Factors that impact on employees’ competency at Johawaki Holdings Sdn Bhd / Mohd Rizal Abd Ghani - Abd Ghani, Mohd Rizal (2014)
The purpose of this study is to determine the impact of employees’ competency that contributed by its influential factors at Johawaki Holdings Sdn Bhd. Three factors were developed to describe which factors largely influenced the employees’ competency and relationship among its impact and contributor factors. Data collected will assist researcher to determine the most factor that gives impact on employees’ competency. Other purpose of this research is to determine the significant relationship between variables that generated by SPSS. Data will be analyzed on four tools including frequency analysis, reliability test, correlation and data descriptive statistic. 50 questionnaires have been distributed to the respondent. However positive cooperation by respondents only 40 item of respondents managed to collected while others were not return the questionnaire back within the time allocated. Result of the data shows that most factor that contribute to employees’ competency is effectiveness of training course with significant value of 0.53